Communications, Signal Processing, and Systems Proceedings of the 2016 International Conference on Communications, Signal Processing, and Systems - Liang, Qilian; Mu, Jiasong; Wang, Wei.; Zhang, Baoju; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book brings together papers presented at the 2016 International Conference on Communications, Signal Processing, and Systems, which provides a venue to disseminate the latest developments and to discuss the interactions and links between these multidisciplinary fields. Spanning topics ranging from communications to signal processing and systems, this book is aimed at undergraduate and graduate students in electrical engineering, computer science and mathematics, researchers and engineers from academia and industry as well as government employees (such as NSF, DOD and DOE).
Wireless communications -- Wireless networks -- Internet of Things -- Wireless sensor networks -- Signal processing for communications and networking -- Audio and acoustic signal processing -- Bio imaging and signal processing -- Machine learning for signal processing -- Sensor array and multichannel signal processing -- Design and implementation of signal processing systems -- Circuits and Systems for Communications -- Neural Networks and Systems -- Fuzzy Logic Systems -- Nonlinear Systems for Communications and Signal Processing.
Keywords: Telecommunication; Electronic circuits; Signal processing; Communications Engineering, Networks; Electronic Circuits and Systems; Signal, Speech and Image Processing